A Comparison of a Traditional Clinical Experience to a Precepted Clinical Experience for Baccalaureate-Seeking Nursing Students in Their Second Semester. (22nd April 2012) - Ownby, Kristin; Schumann, Renae; Dune, Linda; Kohne, David
Abstract : The shortage of nursing faculty has contributed greatly to the nursing workforce shortage, with many schools turning away qualified applicants because there are not enough faculty to teach. Despite the faculty shortage, schools are required to admit more students to alleviate the nursing shortage. Clinical groups in which preceptors are responsible for student learning extend faculty resources. Purpose. To determine the effectiveness of an alternative clinical experience (preceptorship). Methods. quasi-experimental, randomized, longitudinal design. Students were randomized to either the traditional or precepted clinical group. The clinical experience was a total of 12 weeks. Groups were compared according to several variables including second semester exam scores, HESI scores, and quality and timeliness of clinical paperwork. Sample. Over a two-year period, seventy-one undergraduate nursing students in the second semester medical-surgical nursing course participated. 36 were randomized to the experimental group. The preceptors were baccalaureate-prepared nurses who have been practicing for at least one year. Setting. Two hospitals located in the Texas Medical Center. Statistical Analysis. Descriptive statistics and independent t -test. Results. There was no difference between the groups on the variables of interest. Conclusion. Students in the precepted clinical group perform as well as those in a traditional clinical group.